2015
DOI: 10.1002/ets2.12060
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Internal Structure of the Test of English‐for‐Teaching (TEFT™)

Abstract: ELTeach is an online professional development program developed by Educational Testing Service (ETS) in collaboration with National Geographic Learning. The ELTeach program consists of two courses: English‐for‐Teaching and Professional Knowledge for English Language Teaching (ELT). Each course includes a coordinated assessment leading to a score report and certificate for teachers of English as a foreign language (EFL). The Test of English‐for‐Teaching (TEFT™), the assessment component of the English‐for‐Teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Many previous studies aimed at validating constructs of EAP tests have provided some justification for test score interpretations with CFA results as supporting evidence in different contexts (Bachman & Palmer, 1981, 1982Gu et al, 2015;Sawaki et al, 2009;Yan et al, 2019). For example, Sawaki et al (2009) conducted an item-level CFA and identified a higher-order factor model with a higher-order general factor (ESL/EFL ability) and four first-order factors (reading, listening, speaking, and writing) as the best-fitting model for the TOEFL iBT.…”
Section: Cfa Studies On Eap Assessmentmentioning
confidence: 99%
“…Many previous studies aimed at validating constructs of EAP tests have provided some justification for test score interpretations with CFA results as supporting evidence in different contexts (Bachman & Palmer, 1981, 1982Gu et al, 2015;Sawaki et al, 2009;Yan et al, 2019). For example, Sawaki et al (2009) conducted an item-level CFA and identified a higher-order factor model with a higher-order general factor (ESL/EFL ability) and four first-order factors (reading, listening, speaking, and writing) as the best-fitting model for the TOEFL iBT.…”
Section: Cfa Studies On Eap Assessmentmentioning
confidence: 99%
“…In contrast to such a large-scale question, some studies such as Cady and Rearden (2009) (n = 8), provide a fine-grained analysis of such responses. Other studies, like Chapman et al (2010) and Gu et al (2015), explore a particular aspect or question but in the context of a large-scale project. Although very different in focus and design, these types of studies both large and small provided beneficial findings about teacher thinking and teacher change, perhaps as a result of participation in oTPD.…”
Section: Advances In Otpd Researchmentioning
confidence: 99%
“…Kibler and Roman (2013) were interested in teachers' thinking about native language use in the classroom. Researchers were also interested in how both pedagogical tools (e.g., test structure, Gu et al, 2015) and pedagogical practices (e.g., adopting problem-based learning, ) could be successfully managed and implemented in online formats. Repeated findings in these studies include the tensions experienced by teachers shifting from in-person to online formats, the role of facilitators, and questions about the complexity of tasks required online, teacher connection, and reflection (Park et al, 2013;Dana et al, 2017).…”
Section: Attention To the Physical And Pedagogical Layer Of Otpdmentioning
confidence: 99%
“…Specifically, structural validity demands that the internal structure of the measurement scale be consistent with the theoretical structure of the construct that the scale purports to measure [3]. According to Gu, et al [4].…”
Section: Validity As a Unified Conceptmentioning
confidence: 99%
“…When criterion referencing testing (CRT) was introduce in Botswana in 1997 [4], each examinable subject was assessed by means of dimensions that were generated by a panel of subject experts. Although the dimensions had intuitive meaning, there were no studies done to test their psychometric validity.…”
Section: Rationale For the Studymentioning
confidence: 99%